ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI PADI SAWAH DI DESA KAMBUHAPANG KECAMATAN LEWA KABUPATEN SUMBA TIMUR - Olivia Vivilianty Titin Pekawolu; Elfis Umbu Katongu Retang; Elsa Christin Saragih (Universitas Galuh, 2022)
This study aims to determine the factors that influence the production of lowland rice farming in Kambuhapang Village, Lewa District, East Sumba Regency. The method of determining the research area was carried out by purposive sampling, which was determined deliberately, namely in Kambuhapang Village, Lewa District, East Sumba Regency, with the consideration that Kambuhapang Village is one of the areas with the majority of the population working as lowland rice farmers, and being one of the centers for lowland rice plants in Lewa District. The number of samples in this study were 82 farmers. This research uses Multiple Linear Regression analysis and Cobb-douglass production function analysis. The results of this study indicate that partially (respectively) land area, and urea fertilizer have a significant effect on the amount of lowland rice production. Meanwhile, seeds, NPK fertilizers, liquid fertilizers, pesticides, and labor did not significantly affect the amount of lowland rice production. Simultaneously (together) land area, seeds, urea fertilizer, NPK fertilizer, liquid fertilizer, pesticides, and labor have a significant effect on the amount of lowland rice production.